Painted Pillars in the Mandapa of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Closer view of the painted pillars in the mandapa (pillared hall) of the Bhandasar Temple. Between the two central pillars near the antarala (antechamber), there is a low pedestal where devotees perform their daily rituals.